Security Threats and Existing Solutions on Cloud Computing - Shahzad, Faisal; Din, Roshidi; Ghazali, Osman (International Journal of Engineering and Technology, 2018)
Cloud computing as the greatest evolution of distributed computing, gets benefitted from the technology advancement due to its data versatility and economies of scale. Cloud computing aims to offer flexible services that can minimize the customer's need for investing in new hardware and software. However, the rapid extension of cloud computing raises some concerns regarding security and privacy of data that appears to be an inhibitor in the adoption of cloud services. It is, therefore, necessary to address these issues and their existing solutions. For this purpose, the present study is engrossed in the security threats to data that have been listed as the top threats in the previous years. Mainly, this study provides a review of top threats to cloud security and the solutions based on different models, frameworks, and algorithms to ensure data security in a cloud environment. The significance of this paper is twofold as it provides an overview of security threats as well as it explores the existing solutions to the problem in data security in cloud computing. The outcomes of this study presented that there is still a need for accurate mechanism or technique that can minimize the security threats faced in cloud computing.Â Â Â